“El juego como estrategia lúdica de evaluación de la lateralidad, mediante el Test de Harris en niños de 5 años”. - Congo Pabón, Brenda Maritza (2024)
The current research, entitled "Play as a ludic strategy for laterality assessment through the Harris Test in 5-year-old children," intends to supply a different replacement for assessing laterality through play. It has been established that preschool-aged children do not have a determined laterality, as learning centers do not involve in activities to strengthen it. Thus, the aim of this study is to plan a ludic approach based on the Harris Test for the correct assessment of laterality in 5-year-old children from chosen educational institutions in the Zumbahua parish during the 2023-2024 school year. Consequently, a qualitative investigation was performed, employing field research and descriptive, inductive, historical, and bibliographic methods, as it builds upon the realness and encounter of children in their lateralization process. To gather information, observation and interviews were carried out using their respective instruments: checklists and interview guides. As a summary, it was established that early assessment of children as a proactive action is fundamental to accomplishing their integral development, emphasizing the atmosphere as an essential factor contributing to the lateralization process. If the environment devoid stimulation and reinforcement, difficulties in daily actions will be perceived, promoting challenges such as literacy, spatial orientation, language, and so on.